(untitled) (TEST Antologia di Diritto Pubblico, 2026)
This is the reproduction of an excerpt from the study by Massimo Severo Giannini (1915–2000) on the interpretation of administrative acts, published in 1939 and republished in 2000. In particular, the contribution highlights the autonomy of the interpretation of administrative acts from the criteria applicable to other acts such as contracts and statutes.